Effects of cooking methods on the physicochemical, textural and microstructural properties of hot salt puffed germinated brown rice - Saksit Sonsomboonsuk; Tiraporn Junyusen; Pornpimol Moolkaew; Payungsak Junyusen; Tawarat Treeamnuk; Peerawat Taengsopha; Natthaporn Chatchavanthatri; Siriwan Nawong; Phakkhananan Pakawanit (Journal of Agriculture and Food Research, 2024)
This research investigates the effect of cooking methods prior to puffing on the quality of puffed germinated brown rice (GBR). The cooking methods include parboiling and steaming (PS), electric rice cooking (EC), ultrasonic pretreatment and parboiling and steaming (UPS), and ultrasonic pretreatment and electric rice cooking (UEC). The quality metrics are the physical, chemical, textural and microstructural properties of the puffed GBR. The hot salt puffing process was used to expand GBR. The results showed that EC and UEC significantly reduced the bulk density (0.30 g/mL compared with 0.36 g/mL for PS and 0.35 g/mL for UPS) and length/breadth ratio (2.55 compared with 3.21 for PS and 2.89 for UPS) of puffed GBR (p < 0.05), indicative of higher expansion. Besides, the compact structure of non-puffed EC and UEC GBR induced high internal pressure during puffing, resulting in highly porous and hollow microstructure with large pores in puffed EC and UEC GBR. However, the puffed yields of the EC and UEC methods were significantly lower than the PS and UPS methods. The physical and textural properties of puffed UEC GBR were comparable to puffed EC GBR. The decrease in the ratios of the integral areas of crystalline to amorphous peaks of puffed GBR demonstrated that puffing primarily affected carbohydrate structures, as evidenced by reduced crystallinity of puffed GBR. Essentially, electric rice cooking holds promising potential as a cooking method to improve the expansion and textural properties of puffed GBR.